Contribution to the systematic knowledge of Lamium multifidum and L. orientale (Lamiaceae) - Atasagun, Bayram; Aksoy, Ahmet; Martin, Esra (Phytotaxa, 2015)
Some morphological, anatomical, palynological and karyological features of Lamium multifidum and L. orientale (Lamiaceae) naturally occurring in Turkey have been studied. Additional information was added to the previous description of these species. Anatomically, both L. multifidum and L. orientale had an annual taproot, stems quadrangular in cross-section, leaves bifacial. The nutlets were ovoid in outline and trigonous in cross section, blackish-dark brownish, with glabrous surface. The pollen grains of both species were tricolpate, shape subprolate, ornamentation reticulate. In both species, the somatic chromosome number resulted 2n = 14. The anatomical and palynological features, chromosome number and morphological characters of both species were reported for the first time in this study.